The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1186/s13000-019-0797-1
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma arising in a Giant congenital melanocytic nevus: two case reports

Abstract: Background A giant congenital melanocytic nevus (GCMN) is found in 0.1% of live-born infants. If present, the lesion has a chance of about 6% to develop into malignant melanoma. Both children and adults can be affected by malignant melanoma arising in a giant congenital nevus. Up to 95% of GCMNs harbor NRAS mutations, and mutations in the BRAF , MC1R , TP53 , and GNAQ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 40 publications
(50 reference statements)
1
28
0
2
Order By: Relevance
“…Recently, melanoma arising in a giant congenital nevus during the first month of life complicated with neurocutaneous melanosis was found to be associated with only a non-pathogenic P72R polymorphism of the TP53 gene in the homozygote condition. 31 Additionally, P72R polymorphisms were suggested to be associated with an increased plasma cell myeloma risk 32 as well as chronic lymphocytic leukemia. 33 A possible trend towards worse overall survival among patients with P72R polymorphism was mentioned in patients with acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, melanoma arising in a giant congenital nevus during the first month of life complicated with neurocutaneous melanosis was found to be associated with only a non-pathogenic P72R polymorphism of the TP53 gene in the homozygote condition. 31 Additionally, P72R polymorphisms were suggested to be associated with an increased plasma cell myeloma risk 32 as well as chronic lymphocytic leukemia. 33 A possible trend towards worse overall survival among patients with P72R polymorphism was mentioned in patients with acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…A connection between P72R polymorphism and various cancers was reported in current literature. Recently, melanoma arising in a giant congenital nevus during the first month of life complicated with neurocutaneous melanosis was found to be associated with only a non‐pathogenic P72R polymorphism of the TP53 gene in the homozygote condition . Additionally, P72R polymorphisms were suggested to be associated with an increased plasma cell myeloma risk as well as chronic lymphocytic leukemia .…”
Section: Discussionmentioning
confidence: 99%
“…Larger CMNs are associated with an increased risk of malignant transformation to melanoma. It has been reported that malignant transformation presents before puberty or in childhood [ 11 , 12 ]. Therefore, treatment is targeted at effective removal of as many melanocytes as possible at an early age to decrease the risk of malignant transformation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternate treatment options include combinations lasers (diode, fractional carbon dioxide and q-switched Nd-YAG lasers) and curettage. 4,6,7 Compared to adults, pediatric melanomas have more atypical features, thicker lesions at diagnosis, higher frequency of nodular histotype and more aggressive course [Table 1]. 1 A mutational analysis concluded that sun-induced pediatric melanomas exhibit a UV-induced mutational spectrum similar to its adult counterpart (telomerase reverse transcriptase-promoter (TERT-p), BRAF V600 and phosphatase and tensin homolog (PTEN) mutations).…”
mentioning
confidence: 99%
“…Giant congenital melanocytic nevus is characterized by a diameter exceeding 20 cm by adulthood and is associated with 5-40% life-time risk of developing melanoma at the lesional site, most occurring within the first 5 years of life. 3,4 Neuromelanosis and melanoma are more likely with size >40 cm, number >20 or multiple satellite lesions and a truncal location. A gadoliniumenhanced screening magnetic resonance imaging (MRI) of the brain and whole spine is recommended <1 year age in a child presenting with this condition.…”
mentioning
confidence: 99%